Improving the Urban Planning of the Green Zones in Al-Dammam Metropolitan Area, KSA, Using Integrated GIS location-allocation and Accessibility Models - Ashraf Abdelkarim (Geosfera Indonesia, 2020)
In the present study, the location-allocation and the accessibility models of GIS were integrated with the urban planning standards of the Ministry of Municipal and Rural affairs of Kingdom of Saudi Arabia (KSA) in order to enhance the spatial planning and the environmental sustainability of the green zones in Al-Dammam Metropolitan area, KSA. The integration of these models provides a framework for investigating the efficiency of the spatial distribution of the green zones and generating alternatives either by suggesting new effective service or by improving an existing one. To achieve these purposes, the accessibility within (5, 10 and 15) minutes to the service areas in the green zones that is classified into nine types (â€œneighborhood gardensâ€, â€œspecialized parksâ€, â€œcities gardensâ€, â€œchildrenâ€™s gardensâ€, â€œdistrict gardensâ€, â€œstreets and squares gardensâ€, â€œsports cityâ€, â€œSports clubsâ€ and â€œPlaygroundsâ€) was analyzed through analyzing the network structure of the green zones in Al-Dammam Metropolitan area. The location-allocation model was used based on the maximum coverage within response time of no more than 10 minutes.The study revealed poor distribution of the green zones, the low per capita green zones rates with only (3.52 m2/person) and there were no green zones in 45 districts representing 33.3% of the total districts in the investigated area. Consequently, Al-Dammam Metropolitan area suffers from the weakness of the green zones structure and the shortage in fulfilling the needs of population. The current needs were determined as nine services by two â€œsports citiesâ€, two â€œsports clubsâ€, two â€œstreets and Squares gardensâ€, one â€œdistrict gardenâ€, one â€œchildrenâ€™s gardenâ€ and one â€œspecialized parkâ€. It is recommended that the results of this study be taken into consideration by the decision makers while developing the urban planning strategies for improving the infrastructure efficiency as the KSA vision 2030. Keywords: Urban planning; environmental sustainability; green zones; accessibility; location-allocation models; fair and efficient spatial distribution; KSA vision 2030. Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License